Taking Place : Photographs from the Prentice & Paul Sack Collection - Benezra, Neal; Keller, Corey; Nickel, Douglas R.; Phillips, Sandra S.; Sack, Paul; Trachtenberg, Alan; Exhibition. Taking Place : Photographs from the Prentice & Paul Sack Collection. SFMOMA (San Francisco Museum of Modern Art) San Francisco. 2005-06-02. 2005-09-06 (San Francisco : SFMOMA (San Francisco Museum of Modern Art) San Francisco, 2005)
Abbott, Berenice ; Adams, Ansel ; Adams, Robert ; Altobelli, Gioaccino ; Anderson, James ; Arbus, Diane ; Armistead, George ; White, Henry ; Atget, Eugène ; Baldus, Edouard ; Baltz, Lewis ; Barnard, George N. ; Bayard, Hippolyte ; Bing, Ilse ; Bonfils, Félix ; Bosse, Henry P. ; Bourke-White, Margaret ; Brady, Mathew ; Brandt, Bill ; Brassaï ; Bruehl, Martin ; Butterfield, David W. ; Callahan, Harry ; Cameron, Julia Margaret ; Carroll, Lewis ; Cartier-Bresson, Henri ; Charnay, Désiré ; Clifford, Charles ; Langdon Coburn, Alvin ; Crawford, Ralston ; Cunningham, Imogen ; Dane, Bill ; Dassonville, William Edward ; Davidson, Bruce ; De Carava, Roy ; Demachy, Robert ; Eakins, Thomas ; Eggleston, William ; Engel, Morris ; Erwitt, Elliott ; Evans, Walker ; Faurer, Louis ; Feininger, Andreas ; Frank, Robert ; Friedlander, Lee ; Gedney, William ; Genthe, Arnold ; Gilpin, Laura ; Goldin, Nan ; Gutmann, John ; Hagemeyer, Johan ; Hák, Miroslav ; Henri, Florence ; Huberland, Morris ; Jackson, William Henry ; Kertesz, André ; Klein, William ; Klutis, Gustave ; Koudelka, Josef ; Krull, Germaine ; Kwilecki, Paul ; Lange, Dorothea ; Lartigue, Jacques-Henri ; Laughlin, Clarence John ; Levitt, Helen ; Lissitzky, El ; Lyon, Danny ; Maar, Dora ; Man Ray ; Mantz, Werner ; Matta-Clark, Gordon ; Meatyard, Ralph Eugene ; Meiselas, Susan ; Metzker, Ray K. ; Miller, Lee ; Model, Lisette ; Moholy-Nagy, Laszlo ; Morris, Wright ; Munkacsi, Martin ; Outerbridge, Paul ; Owens, Bill ; Parks, Gordon ; Renger-Patzsch, Albert ; Rodchenko, Alexander ; Rothstein, Arthur ; Sander, August ; Seeley, George Henry ; Shahn, Ben ; Sheeler, Charles ; Sinsabaugh, Art ; Smith, William Eugene ; Stackpole, Peter ; Stankowski, Anton ; Steichen, Edward ; Steiner, Ralph ; Stettner, Louis ; etc.
Catalogue of the Exhibition + biog. p. 235-241
Engels
boek